Seasonal decoupling of particulate organic carbon export and net primary production in relation to sea‐ice at the shelf break of the eastern Bering Sea: Implications for off‐shelf carbon export. Issue 10 (18th October 2013) - Baumann, M. S.; Moran, S. B.; Lomas, M. W.; Kelly, R. P.; Bell, D. W.
<x xml:space="preserve">Abstract</x> [1] Particulate organic carbon (POC) export fluxes and net primary production (NPP) rates are used to assess seasonal patterns in the export ratio (e‐ratio = POC export/NPP) in relation to proximity of the sea‐ice edge near the shelf break of the eastern Bering Sea during 2008–2010. POC fluxes were relatively low in April (4.6 ± 1.6, trap, and 5.7 ± 4.3 mmol C m−2 d−1, 234Th‐derived) and increased in May–early June (19.9 ± 13.3 and 17.0 ± 8.8 mmol C m−2 d−1). POC export reached a maximum in mid‐June–mid‐July (30.0 ± 12.6 and 48.1 ± 17.4 in 2009; 33.1 ± 27.6 and 57.0 ± 68.4 mmol C m−2 d−1 in 2010) and decreased by late July (13.1 ± 4.7 and 14.1 ± 8.0 mmol C m−2 d−1). NPP rates were relatively high and export fluxes low near the ice‐edge in spring leading to e‐ratios <0.25. In early summer, POC export exceeded NPP at individual stations and resulted in e‐ratios >1, which is attributed to a temporal decoupling, or offset, of spring NPP and export during summer. While these observations reveal a seasonal progression in POC export and the e‐ratio, there is no direct relationship to sea‐ice proximity. Furthermore, based on a water column‐sediment 234Th budget, the off‐shelf export of POC during spring‐summer is estimated to be 24 ± 35 mmol C m−2 d−1, which represents an off‐shelf e‐ratio of 0.07 and 0.21 for contemporaneous seasonally averaged daily NPP and 0.17 and 0.52 for historical monthly averaged daily NPP. An implication is that off‐shelf POC transport may represent a seasonal net sink for CO2 in this and other polar shelf regions.